Cataloging minerals, part 1: The categories of colonialism and extraction - Selby Hearth; Carrie Robbins (Museum & Society)
Mineral wealth has motivated and funded extractionist empires, often at the expense of local communities, labor, environments, and public health. Yet those connections are not recorded in traditional mineral catalogs, which treat specimens as divorced from context. This essay examines the roots of those omissions, and situates mineral cataloging in the larger body of literature on knowledge organization systems and power. We examine how colonial ideologies of land and people become entrenched in mineral cataloging practices, and how this reinforces the ways geologists think about their work. We argue that revising mineral cataloging practices is a necessary first step – both practically and epistemically – toward addressing histories of violence in our mineral collections and the science of geology as a whole.